Sensitization of pulmonary chemosensitive neurons by bombesin-like peptides in rats - Gu, Qihai (2005)
Small cell lung cancer (SCLC) patients suffer from pulmonary stresses such as dyspnea and chest pain, and the pathogenic mechanisms are not known. SCLC cells secrete a variety of bioactive neuropeptides including bombesin-like peptides. We hypothesize that these peptides may enhance the sensitivity of the pulmonary chemosensitive nerve endings, contributing to the development of these pulmonary stresses in SCLC patients. This study was therefore carried out to determine the effects of bombesin and gastrin-releasing peptide (GRP), a major bombesin-like peptide, on the sensitivities of pulmonary chemoreflex and isolated pulmonary vagal chemosensitive neurons. In anesthetized, spontaneously breathing rats, intravenous infusion of bombesin or GRP significantly amplified the pulmonary chemoreflex responses to chemical stimulants such as capsaicin and ATP. The enhanced responses were completely abolished by perineural capsaicin treatment of both cervical vagi, suggesting the involvement of pulmonary C-fiber afferents. In isolated pulmonary vagal chemosensitive neurons, pretreatment with bombesin or GRP potentiated the capsaicin-induced Ca(2+) transient. This sensitizing effect was further demonstrated in patch-clamp recording studies; the sensitivities of these neurons to both chemical (capsaicin and ATP) and electrical stimuli were significantly enhanced by the presence of either bombesin or GRP. In summary, our results have demonstrated that bombesin and GRP up-regulate the pulmonary chemoreflex sensitivity in vivo and the excitability of isolated pulmonary chemosensitive neurons in vitro.